2002
DOI: 10.1055/s-2002-23140
|View full text |Cite
|
Sign up to set email alerts
|

Deoxypodophyllotoxin; The Cytotoxic and Antiangiogenic Component from Pulsatilla koreana

Abstract: The petroleum ether fraction of Pulsatilla koreana (Ranunculaceae) was found to have an inhibitory effect on the tube-like formation of human umbilical venous endothelial (HUVE) cells and strong cytotoxic activity against five tumor cell lines. The active component isolated from the fraction was deoxypodophyllotoxin (DPT). The cytotoxic activity against the tumor cells comprising the A549, SK-OV-3, SK-MEL-2, HCT15, and B16F10 cell lines, expressed as ED50, ranged from 6 to 18 ng/ml. 3 ng/ml of DPT, a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 5 publications
3
46
0
1
Order By: Relevance
“…Stock solutions were mixed to obtain the desired concentrations. The mixed stock solutions were then diluted in 50% methanol in the concentration ranges of 2 -200 µg/mL (2,4,8,20, 40, 80 and 200 µg/mL) for pulsatilloside E, anemoside B4, and cussosaponin C, and 5 -500 µg/mL (5, 10, 20, 50, 100, 200 and 500 µg/mL) for pulsatilla saponin H. All solutions were stored at 5 o C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stock solutions were mixed to obtain the desired concentrations. The mixed stock solutions were then diluted in 50% methanol in the concentration ranges of 2 -200 µg/mL (2,4,8,20, 40, 80 and 200 µg/mL) for pulsatilloside E, anemoside B4, and cussosaponin C, and 5 -500 µg/mL (5, 10, 20, 50, 100, 200 and 500 µg/mL) for pulsatilla saponin H. All solutions were stored at 5 o C.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7] Previous chemical and pharmacological investigations have revealed that triterpenoid saponins are its main biologically active components, exhibiting antitumor, cytotoxic, cognition-enhancing and other effects. [8][9][10] Recently, the saponin fraction of P. koreana was reported to improve memory impairments, and clinical trials for treatment of Alzheimer's disease using this fraction are in progress in Korea. 11,12 As noted above, triterpenoid saponins represent the major biological activities of P. koreana and these saponins could be used as chemical markers for quality control.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Oleanane-type triterpenoid saponins, lupane-type triterpenoid saponins, quinones, phenylpropanoids, and flavonoid glycosides have been isolated from the root and aerial parts of P. koreana in previous phytochemical studies. [5][6][7][8][9] However, there have been few studies that have specifically aimed to identify compounds from the flowers of P. Koreana.…”
Section: Introductionmentioning
confidence: 99%
“…Also, PKE has been found to have prominent neuroprotective abilities to reverse scopolamine-induced cognitive impairment in rats (10). In addition, several studies have been reported that components of PKE were effective in preventing cancers cells including melanoma and ovarian cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%